Influence of school climate on the formation of leadership as a personality trait in high school students - Prada Martínez, Leonardo (Rastros Rostros, 2024)
Introduction: The school environment significantly influences the formation of personality traits of students in secondary school, as part of the comprehensive training process promoted by public educational policy, with leadership found in the literature as a variable of interest for the promotion of future social leaders. Objective: To analyze the influence of the school climate on the formation of leadership as a personality trait in high school students at an educational institution in Cartagena de Indias (Colombia). Methodology: This research is based on a quantitative approach and uses a non-experimental design of explanatory scope, with the participation of 192 students from the secondary school of a public educational institution in Cartagena, to whom the Dweck Mindset Instrument was applied to measure the leadership of the participants. Results and discussion: No significant differences were found by gender, being an only child, family location, migration or abandonment (p = 0.76). However, significant correlations were found between grade, age and family economic status, and leadership patterns (p = 0.000). It was evident that camaraderie and the institutional regulatory environment act as mediators between the school climate and leadership as a personality trait of the student body. In addition, significant differences were observed in leadership patterns according to age, level of education and family economic situation (p = 0.002). Additional analysis showed that 6th graders exhibited a significantly higher level of leadership than 7th, 8th, and 9th graders, and overall, the level of leadership tended to decrease with increasing grade. Conclusions: Based on the Colombian school context, this study has practical implications for improving leadership as a personality trait of high school students, taking into account that this school period is critical in the development of students’ self-identity, which can be easily influenced by situational factors.